Digital Discourse And Cultural Narratives: A Corpus-Based Analysis Of Coffee Tourism In Indonesia On Twitter - Moch Fuad Nasvian; Hamdan Nafiatur Rosyida; Christian Sri Kusuma Aditya (FAKULTAS DAKWAH UIN SALATIGA, 2025)
Public discourse on social media can provide marketing communication strategists with deeper insights for crafting relevant and relatable content. This study explores how Indonesian Twitter users discursively construct narratives around coffee tourism through user-generated content (UGC). Using a corpus of 37,553 tweets posted between February 2024 and January 2025, the study applies computational content analysis, including keyword-in-context (KWIC), co-occurrence mapping, and collocate analysis via Voyant Tools. The findings show that the term “kopi” (coffee) frequently appears alongside affective and experiential keywords such as “enak” (delicious), “liburan” (holiday), and “kebun” (plantation), reflecting coffee’s symbolic role in leisure, identity, and place-making. These discursive patterns highlight the shift from traditional promotion to participatory tourism storytelling. This study contributes to communication scholarship by illustrating how digital discourse reflects public meaning-making, and offers practical insights for destination branding through audience-centered content strategies rooted in cultural and emotional resonance.